Immigrant attraction through place branding? Evidence of city-level effectiveness from Canada's London. (February 2020) - Cleave, Evan; Arku, Godwin
Highlights: In Canada, immigration is increasingly vital to offset stagnant population growth and a declining domestic labour force. Increasingly, cities are using place branding to attract immigrants. Place branding appears to be effective in changing immigrant perceptions and facilitating the decision of where to live. Abstract: To stabilize and grow their local economies, cities in Canada and other advanced economic regions have begun using place branding to attract high-skilled and well-educated immigrants. This is part of a larger trend where place branding is viewed as a necessary undertaking to respond to local issues. Despite the increased attention, there is considerable uncertainty over whether place branding is effective. To address this question, this research investigates place branding's role in influencing immigrant place perception and decision-making on where to live. A seven-factor model was used to capture 739 evaluations of the City of London, Canada and five other cities in the Province of Ontario. Responses were analyzed with ANOVA contrast tests and multivariate regression to identify differences in place and brand perceptions between the five cities. Findings identified that immigrant views of the cities differed and influenced decision-making on where to live. Interestingly, perceptions about the economy and housing were the key drivers of the evaluation of cities, rather than traditional branding and promotional efforts. The implication is that cities need to be strategic in their branding efforts to ensure they promote the features of the city that are meaningful to the target audiences being pursued.